Development of Marine Loading and Unloading System for Ro-Ro Vessel - Amiadji Amiadji; Sunarsih Sunarsih; Arie Nanda Rizaldi (Institut Teknologi Sepuluh Nopember, 2019)
Ship stability is one of the important criteria for ship safety as required by IMO and Indonesia Classification Bureau (BKI) in various rules. One of it is the IMO code of Intact Stability. Many factors affect the stability of a ship, including ship load, which in application varies in weight and type of vehicle. Maxsurf has been used to analyze various conditions of the ship, including stability. However, Maxsurf is too complicated to be used by ordinary people. For that a package needed as mediator to Maxsurf to be easier to use. This research developed a package to assist in analyzing the ship stability with vary in weight and type of vehicle. The package was created in Microsoft Excel worksheet and is connected to Maxsurf Stability. Visual Basic for Application was use to write the codes (coding) for the package command. The target ship used in this analysis is a 500 GT ferry ship. After the package is working properly, the analysis simulation can be run. Simulation results show that maximum GZ of both fully loaded and overloaded conditions occur at tilt angle of around 30o. Exceeding such value, the ship for both conditions slowly lose the turning moment. At fully loaded condition, the ship hardly turns back after reaching a tilt angle of 73 o. At overload condition, the ship is still safe though losing its ability to turn back is faster, at heel angle of 71o.